Advanced Micro‐Lattice Materials1. Issue 9 (4th February 2015) - Xiong, Jian; Mines, Robert; Ghosh, Ranajay; Vaziri, Ashkan; Ma, Li; Ohrndorf, Arne; Christ, Hans‐Jürgen; Wu, Linzhi
<x xml:space="preserve">Abstract</x> Topological management of materials at a Micro‐scale is one of the fundamental building principles of nature. This combination of material and structural properties results in marked changes in the properties of solids. Nowadays physicists, chemists, materials scientists and engineers explore those effects by synthesizing, characterizing, and modeling Micro‐lattice materials from all material classes. Applications have been identified in the fields of ultra‐lightweight structures, thermal equipment, electrochemical devices, high absorption capacity and bio‐repair materials. This article aims to review recent progress in the development of such advanced Micro‐lattice materials.